Youth and Suicide in American Cinema Context, Causes, and Consequences - Seggi, Alessandra (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book explores the depiction of suicide in American youth films from 1900 to 2019. Anchored in Sociology, this multidisciplinary study investigates the causes and consequences of suicide and uncovers the socio-cultural context for the development of youth, film, and suicide. While such cinematic portrayals seem to privilege external explanations of suicide versus internal or psychological ones, overall they are neither rich nor sensitive. Most are simplistic, limited or at the very least unbalanced. At times, they are flatly controversial. In light of this overall problematic depiction of suicide, this book offers a proactive approach to empower young audiences-a media literacy strategy to embrace while watching these films. Alessandra Seggi is a Fulbright scholar and an award-winning artist. At Temple University, USA, her research and teaching focus on the intersection of the social sciences and media. She is currently working on an innovative project combining drawings with rhymes and traditional texts to illustrate the key dynamics of social life.
Part I: Theory, Context & Terms of Reference: Youth, Film, Suicide & Media Literacy -- 1. Theory: Theoretical Bricolage -- 2. Context: It's Complicated -- 3. Terms of Reference -- 3.1 Terms of Reference. After Childhood: Teenagehood, Puberty, Adolescence & Youth -- 3.2 Terms of Reference. Film -- 3.3 Terms of Reference. Suicide -- 3.4 Terms of Reference. Self-harm -- 3.5 Terms of Reference. Media Literacy -- Part II: Youth & Suicide in American Cinema -- 4. Rationale & Scope: Film Selection & Sampling -- 4.1 Scope & Criteria for Movie Selection -- 4.2 Details about Film Selection -- 4.3 The Importance of Studying the Representation of Suicide in Youth Films -- 5. Films Depicting Youth & Suicide: Part I -- 6. Films Depicting Youth & Suicide: Part II -- 7. Dilemmas & Dichotomies About Suicide and Youth in Film -- 8. A Foil & a Game Changer: Archie's Final Project -- 8.1 Discussions of Form -- 8.2 Discussions of Content -- 8.3 The Bigger Picture: The Teen Condition & the Human Condition -- 9. A Conundrum, Evolving: 13 Reasons Why -- Part III: A Proactive Approach: Media Literacy Strategy -- 10. Tools of the Trade: Media Influence, Media Guidelines & Media Literacy -- 11. A Proactive Approach: A Media Literacy Strategy With Critical Questions for Engaged Audiences -- 11.1 Suicide in Film: Critical Questions for Engaged Audiences -- 11.2 Questions in Brief -- 11.3 Questions in Depth -- 12. Media Literacy Strategy in Action: Application of Media Literacy Questions to Sample Films -- 12.1 Archie's Final Project: Allure Versus Accuracy in Its Promotional Material -- 12.2 13 Reasons Why -- 12.3 Other Films.
Keywords: Motion pictures, American; Youth-Social life and customs; Popular Culture; American Film and TV; Youth Culture; Popular Culture